Primary Perivascular Epithelioid Cell Tumor (Pecoma) of Bladder: Case Report and Review of Literature - MD, Rigvardhan; Khanna, MD, Shiv Pankaj; Deb, MD, Prabal (International Journal of Innovative Research in Medical Science, 2018)
Perivascular epithelioid cell neoplasms (PEComas) represent a rare family of neoplasms. Their dichotomous phenotypic features, including both myogenic and melanocytic features can make a definitive diagnosis difficult. So far 15 cases of PEComa urinary bladder have been reported. We describe a case of PEComa bladder for its rarity along with review of literature.